Fasting plasma glucose and serum uric acid levels in the peri‐urban region - Cynthia Tjitradinata; Perigrinus Hermin Sebong; Edward Hartono; Henrita Ernestia; Eviana Budiartanti Sutanto; Alberta Widya Kristanti; To Lidwina Prillya Indra Christyana; Vania Angeline Bactiar (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The prevalence of hyperuricemia has increased, yet there is a gap in empirical studies regarding the association between hyperuricemia and diabetes mellitus in Indonesia. Purpose: To determine the baseline association between serum uric acid and fasting blood glucose in the peri-urban population. Method: A quantitative approach was employed, with particular emphasis on a formative method. The study was conducted in Sampangan, Semarang, from January to April 2023. Uric acid levels served as the independent variable, while fasting blood glucose was designated as the dependent variable. A total of 44 participants were selected through total sampling, based on predetermined inclusion and exclusion criteria. Data analysis involved univariate testing to assess the frequency distribution of participant characteristics, followed by bivariate analysis utilizing one-way ANOVA and Kruskal-Wallis tests. Results: Significant differences were observed in fasting blood glucose, serum uric acid, and systolic blood pressure levels across the healthy, prediabetic, and type 2 diabetic groups, as well as between individuals with normal uric acid levels and those with hyperuricemia. Conversely, no significant differences were found for age, diastolic blood pressure, body mass index (BMI), or cholesterol levels. Conclusion: This study offers a deeper understanding of serum uric acid levels among healthy individuals, prediabetic patients, and individuals with type 2 diabetes mellitus. Factors such as uric acid concentration, presence of hypertension, and patient initiative contribute to decisions regarding the continuation of screening.